– The Effect of The Internal Environment on Knowledge Sharing – Afield Study on Administrative Personnel at The University of Jeddah - Massoudi, Angham Massoud Al Oud; Aldoan, Hamed Mohammed Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2018)
The main objective of this study was illustrate the impact of the internal environmental elements which that includes; organizational structure, organizational culture, leadership, and information technology, on knowledge sharing among administrative employees in Jeddah of University. The study used the descriptive analytical method, wherein a random selection of samples was taken from the study group that represented all the administrative employees in Jeddah of University. A Questionnaire was also drafted for this purpose of collecting data and was distributed to (280) individuals working in Jeddah of University. The number of questionnaires that were fit for analysis reached (249). The results of the study found the presence of an effect at a significance level indication of (p ≤ 0.01) for the elements of the internal environment (organizational structure, organizational culture, leadership, and information technology) on knowledge sharing. The succession of the elements from an impact perspective was leadership, organizational structure, information technology, and organizational culture. In light of the results reached, the study recommended various advice, mainly: the importance of knowledge sharing and the criticality of increasing it in universities and to facilitate the access to knowledge sharing between employees and various administrative departments. As well as, the necessity to work on improving the standards of administrative leadership roles and qualifying them, and to follow the modern leadership styles, so that it can find an internal environment that incorporates compatibility and harmony between the employees. In addition, the importance of exploiting the means of technology at University in a better way and utilizing it for knowledge sharing purposes. Furthermore, the necessity to find an organizational culture that supports and encourages knowledge sharing, and the importance of developing the organizational structure and to develop flexible structures that are capable of dealing with knowledge and its transfer tools.